Loading conditions and neuromuscular activity during vertical knee flexion-extension and turn-like movements in a new skiing simulator under vibration conditions - Pozzo, R.; Zancolò, F.; Canclini, A.; Baroni, G. (Science and Skiing IV, 2009)
INTRODUCTION: In alpine skiing the loading constrains make the legs to resist to high level of peak forces and vibrations (Mueller 2001, Pozzo 2006). This loading conditions are not easy to be reproduced by means of Standard strength exercise used in training protocols. The aim of this study is to verify the dynamic and neuromuscular responses of knee flexion-extension exercises executed with different techniques: vertically (VE) and with leaning the body sideways like to the normal turn movements on the ski (SSE), performed on a new ski Simulator under Vibration conditions. The Simulator used has two breech footboards, with normal ski boots bindings, which can rotate around their longitudinal axis and can vibrate with a frequency between 0 to 50 Hz. The athlete is tied with a waist belt from which two lateral cables and one, directed to middle line of the feet, are connected to a traction lever which is controlled by an external operator